Exploration of the Use of ChatGPT as A Writing Assistance for EFL Students: A Literature Review - Afiliani, Afiliani; Tupalessy, Pricilia; Talaohu, Beby Sinta (MATAI: International Journal of Language Education, 2023)
This article explores the utilization of ChatGPT as a writing assistance for English as a Foreign Language (EFL) students through a comprehensive literature review. This article emphasizes the growing role of artificial intelligence in language education, particularly within the dynamic landscape of EFL, the study employs a descriptive qualitative research design through a literature review method. ChatGPT, developed by OpenAI, stands out for its ability to generate human-like text responses, presenting promising benefits in EFL writing education. These advantages include providing personalized real-time feedback, engaging students through interactive exercises, and fostering personalized learning experiences. However, the review acknowledges critical challenges, such as the potential for inappropriate feedback, over-reliance on ChatGPT, and biases in AI technologies. The study highlights ChatGPT's potential in improving EFL writing but underscores the importance of ethical considerations and effective implementation. Valuable insights are provided for educators, students, and stakeholders seeking a nuanced understanding of ChatGPT's role in language learning.